Indian Media Business. - Kohli-Khandekar, Vanita (Sage Publications Pvt. Ltd, 2013)
The Indian Media Business, Fourth Edition gives you detailed analysis, perspective and information on eight segments of the media business in India-print, TV, film, radio, music, digital, outdoor, and events. It presents the business history, current dynamics, regulation, economics, technology, valuations, case studies, trends (Indian and global) and a clear sense of how the business operates. This book is a must-read for media professionals, students and for those planning to invest in the Indian media and entertainment business. The outstanding feature of the fourth edition is a new chapter o.